Arka . wolne pismo : eseistyka, krytyka, literatura, inne formy, no. 2, 1983 - Polkowski, Jan; Besançon, Alain; Bellow, Saul ([s.n.], 1983)
Creation and circulation: From issue no. 29 (1990) published legally